Transformações Sociais durante o III Milénio AC no Sul de Portugal. O Povoado do Porto das Carretas - Soares, Joaquina (2014)
This publication aims to characterise the Chalcolithic social organisation in the first half of the third millennium BC in Southern Portugal, and to analyse the economical and socialtransformations that took place in the second half of the same millennium. These were related to the decline of the Chalcolithic mode of production in South-Western Iberia. The complex,more centralised and hierarchical Bronze Age societies emerged from the collapse of that social model.The theoretical constructions draw on the empirical record from the archaeological excavations in the settlement of Porto das Carretas(Mourão), that surmount the left bank of Guadiana River. The site has been contextualised both at local (Triângulo da Luz territory) and regional scale (South-Western Iberian Peninsula). From the several factors explaining the process of change, the intensification of production was chosen for this study, as associated with technological and economical innovations. As far as the dawn of the Chalcolithic is concerned, it is necessary to follow the positive effects of the Secondary Products Revolution on the rates of growth of all the indicators of social development, such as productivity, sedentism and population density. For the first half of the third millennium BC, the author proposes a complex tribal organisation model, where the social hierarchy was maintained in the kinship structure. The crisis of the Chalcolithic society gave way, in the second half of the third millennium BC, to more unequal and hierarchical societies (Bell Beaker period), along with the development of copper metallurgy (copper-arsenic alloys) and craft specialisation.